Nationwide distribution and insecticide resistance study of Malaysian mosquito Culex quinquefasciatus say by molecular and biochemical tools / Low Van Lun - Low, Van Lun (2013)
A nationwide investigation was carried out to (1) determine the distribution of Culex quinquefasciatus and other species of mosquitoes in stagnant water in residential areas, (2) investigate the genetic diversity of Cx. quinquefasciatus, (3) quantify the insecticide susceptibility status of Cx. quinquefasciatus, (4) characterize the biochemical mechanisms of insecticide resistance in Cx. quinquefasciatus, (5) characterize the molecular mechanisms of insecticide resistance in Cx. quinquefasciatus from 13 states and one federal territory in Malaysia. Culex larval surveillance indicated that Cx. quinquefasciatus was the predominant species in residential areas. Several habitat characteristics (i.e., pH, conductivity, salinity, total dissolved solids, elevation and dissolved oxygen) were found to be associated with Culex larvae distribution. In the context of molecular phylogeography, the genetic diversity of Malaysian Cx. quinquefasciatus was extremely low since only three and four haplotypes were revealed by COI and COII, respectively. As for insecticide resistance study of Cx. quinquefasciatus, both WHO larval and adult bioassays exhibited dissimilar trends in susceptibility against DDT, propoxur, malathion and permethrin. Correlations between propoxur and malathion resistance as well as between propoxur and permethrin resistance in larval bioassays were found. In enzyme microassays, elevated levels of α- esterases, β-esterases, mixed function oxidases, glutathione-S-transferase and acetylcholinesterase activities were demonstrated in majority of the populations. Besides, a correlation between α-esterases activity and malathion resistance was also demonstrated. An association between activity of α-esterases and β-esterases and between glutathione-S-transferase and acetylcholinesterase was also demonstrated. In addition, genotyping of insensitive acetylcholinesterase revealed the presence of G119S mutation in the wild populations of Cx. quinquefasciatus, but in heterozygous state and at a very low frequency (18 out of 140). Statistical analysis also revealed that malathion resistance was associated with the frequency of ace-1 resistant allele in Cx. quinquefasciatus populations. On the other hand, genotyping of insensitive voltage gated sodium channel revealed the presence of L1014F mutation which was dominated by heterozygous genotype (99 out of 140), followed by three individuals of homozygous genotype. However, no association was found between the frequency of kdr resistant allele and DDT and permethrin resistance. The findings of this study could be utilized in the implementation of strategic measures in vector control programs in Malaysia. Identification of the breeding preferences and population structure of mosquitoes offers an opportunity to elucidate their influence on the current distribution of mosquito species in these study areas and subsequently understand their potential risks in disease transmission. Besides, the bioassay data may also assist local authorities in providing susceptibility baseline and appropriate dosage of larvicide or adulticide to be used during vector control operations. Application of both biochemical and molecular tools provides significant insights into the evolution and adaptation of Malaysian Cx. quinquefasciatus. In conclusion, this study has demonstrated the associations between the Culex distribution and various habitat characteristics. Besides, a phylogenetic relationship among Malaysian Cx. quinquefasciatus was revealed. This study has provided the first evidence for the involvement of target site alterations and detoxification mechanisms in insecticide resistance among Cx. quinquefasciatus populations in Malaysia.